2016
DOI: 10.1038/pr.2016.23
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent copy number variants associated with bronchopulmonary dysplasia

Abstract: Background: Variability in the incidence and severity of bronchopulmonary dysplasia (BPD) among premature infants suggests that genetic susceptibility plays a role in pathogenesis. An assessment of copy number variants (CNV) in BPD subjects may help to identify loci that harbor genetic susceptibility factors. Methods:We conducted a retrospective analysis of clinical DNA microarray data from our institution. We identified 19 BPD subjects, and 2 controls groups (full-term and preterm) with no lung-related diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Further analysis demonstrated that pathways associated with genes differentially methylated and expressed in BPD included ErbB signaling, neuregulin signaling, RhoA signaling, VEGF signaling, cardiomyocyte differentiation via BMP receptors, axonal guidance signaling, and glutathione-mediated detoxification [43]. Some of those pathways such as RhoA signaling, axonal guidance signaling and glutathione-mediated detoxification have been implicated in lung development and BPD pathogenesis [94][95][96]. Other than DNA methylation, histone marker modifications, especially on the outer promoter regions, are important for the epigenetic programming of gene expression [102][103][104] and play a crucial role in the developmental origin of lung diseases [105][106][107][108][109].…”
Section: Epigenetic Programming and Neonatal Chronic Lung Diseasementioning
confidence: 99%
“…Further analysis demonstrated that pathways associated with genes differentially methylated and expressed in BPD included ErbB signaling, neuregulin signaling, RhoA signaling, VEGF signaling, cardiomyocyte differentiation via BMP receptors, axonal guidance signaling, and glutathione-mediated detoxification [43]. Some of those pathways such as RhoA signaling, axonal guidance signaling and glutathione-mediated detoxification have been implicated in lung development and BPD pathogenesis [94][95][96]. Other than DNA methylation, histone marker modifications, especially on the outer promoter regions, are important for the epigenetic programming of gene expression [102][103][104] and play a crucial role in the developmental origin of lung diseases [105][106][107][108][109].…”
Section: Epigenetic Programming and Neonatal Chronic Lung Diseasementioning
confidence: 99%
“…Copy number variants have also been addressed as contributors to BPD susceptibility, where three loci, at 11q13.2, 16p13.3, and 22q11.23-q12.1, that exhibit copy number variants with increased frequency in BPD patients were identified (9). Genes residing within these regions included 15 genes that undergo temporal changes in expression during transition from the pseudoglandular to the canalicular stage, which is a most relevant period of lung development in BPD.…”
Section: L1123mentioning
confidence: 99%
“…Four cases had CNVs at chr22q11.23–q12.1 (chr22:25672585–25903543) involving IGLL3P, LRP5L, CRYBB2P1 , and MIR6817 (three deletions and one duplication). This 22q11.23–q12.1 region is associated with bronchopulmonary dysplasia (BPD) in premature infants [ 86 ] and in our cases is not likely to be related to SUDP, as our cases were not born prematurely. Two cases had duplications at 15q26.2 (chr15:96869390–96950543 and chr15:96869390–96896882) encompassing NR2F2 .…”
Section: Resultsmentioning
confidence: 91%